Pengaruh model pembelajaran discovery learning menggunakan pendekatan STEAM (science, technology, enginering, art, mathematic) terhadap kemampuan berpikir komputasi siswa - Sa'adah, Umi; Faridah, Siti Nur; Ichwan, Muhammad; Nurwiani, Nurwiani; Tristanti, Lia Budi (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
The purpose of this study was to determine the effect of the Discovery Learning learning model using the steam approach (science, technology, engineering, art, mathematics) on students' computational thinking abilities. This type of research is quantitative research with experimental research methods. The population in this study were class VIII SMP A. Wahid Hasyim Tebuireng with a sample of class VIII-I as the experimental class and class VIII-C as the control class. The experimental group was treated using the Discovery Learning model with the STEAM approach while the control group used the conventional model. The instrument used is a test sheet. Data analysis techniques using the t test. Based on the results of the analysis of the data obtained by calculating using IBM SPSS25 between the samples that were given the treatment of the Discovery Learning learning model with the STEAM approach in the experimental class and the control class, the output results were Sig. (2-tailed) of 0.020. This means that the sig value of 0.046 <0.05 means H0 is rejected, so it is said that there are differences in students' computational thinking abilities between those who take the Discovery Learning model learning the STEAM approach and those who take conventional learning. Then there is the influence of the STEAM approach Discovery Learning model on students' computational thinking skills.